Perlindungan Konsumen terhadap Hasil Produksi Kosmetik dan Obat Tradisional melalui Peningkatan Fungsi dan Kewenangan Balai Besar Pengawas Obat dan Makanan (Balai Besar Pom ) Surabaya - Mardi Handono; Ikarini Dani Widiyanti; Pratiwi Puspitho Andini (JURNAL RECHTENS, 2018)
The protection of the law to consumer is a very important thing to be applied in society, because, in reality, consumers would always be wronged. The mighty acts of underhand business operators to profit much has often happened in the community, and this can be seen from the news from the mass media, for example the news of cosmetics products and traditional medicines containing material dangerous may not be used, so as to cause harm moral support and materially, even to have claimed the lives of consumers. Big hall food and drug supervisory Surabaya is one form of consumer protection through their and authority through action supervision pre-market and post market, information on several cosmetics producers and traditional medicines about how processing industry substandard prevailing, giving the cosmetics certification and traditional medicine, supervising cosmetics producers and traditional medicines and do annihilation cosmetics and traditional medicines to consumers.  Keywords : consumer protection, big hall food and drug supervisory surabaya, cosmetics and traditional medicine